Rancang Bangun Website Pemerintahan Desa Guwang sebagai Media Informasi Desa dan Promosi Destinasi Wisata - Jelantik, I Made; Utami, Nengah Widya; Dwi, I Gst. Agung Pramesti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
In the modern era, the utilization of technology and information systems has become one of the most effective tools for disseminating information. Guwang Village, located in Sukawati District, Gianyar Regency, does not yet have a village website, leading to village activities and promotional information being poorly communicated to the wider community. This situation has resulted in the potential of Guwang Village not being widely recognized by either local residents or potential tourists. To address this issue, the Village Government collaborated with Primakara University and the Community and Village Empowerment Agency of Gianyar Regency through the Accelerated Digital Village Program to develop a village website. The primary objective of this initiative is to create a village website as a medium for disseminating information on Village Government activities and promoting the tourism potential of Guwang Village to a broader audience. As a result, a village website containing information on village activities and tourism potential was successfully created and implemented. This website is expected to serve as an effective tool for advancing Guwang Village and attracting more attention from both the general public and tourists.